Storage of Standard Fixed Rabies Virus CVS Strain in Protective Media with Sucrose, Glycerol and Maltose at Diff erent Temperatures During One Year - Varianytsia, Viktoriia V.; Vysekantsev, Igor P. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 153